Representation Of Students' Relational Understanding In Solving Evidence-Related Problems - Marhan Taufik; Reni Dwi Susanti (SJME (Supremum Journal of Mathematics Education), 2022)
The goal of this study is to see how students' relational understanding affects their ability to solve proof problems in basic logic classes. Because this study will illustrate how students' relational knowledge in solving arithmetic problems, it is a qualitative research with a descriptive kind. Tests and interviews were used to gather data, which was then evaluated using research data reduction methodologies, which included presenting data in the form of descriptions based on features of relational knowledge, and finally concluding the findings. The findings revealed that students' relational understanding appeared to be carried out in solving proof problems, specifically in the interpretation aspect, then in the aspect of preparing questions and hypotheses, and finally in the aspect of generalization, all of which were visible when observations were made and were found in the responses of students. However, there are still flaws and inconsistencies in the signs of applying and performing reasoning.